Orientacja prorynkowa w zarządzaniu przedsiębiorstwami - Strużycki, Marian; Szulce, Halina (Digitalizacja i deponowanie archiwalnych zeszytów RPEiS sfinansowane przez MNiSW w ramach realizacji umowy nr 541/P-DUN/2016, 1990)
In order to achieve a high level of economic development it is necessary to work out a pro-market orientation comprising the processes of producing goods for domestic and foreign markets. Then, pro-market orientation is the main determinant of methods to be applied in managing the enterprise and the basis for shaping the regulative processes in the economy. The said orientation brings about certain consequences, both for the development of stock structures as well as for the speed of achieving the economic balance. Of special significance for the latter process is the capacity of the production to adjust to the needs of specific customers, its capacity to retain a high technological level and its capacity to take into account elementary requirements with respect to marketing procedures on given markets. Strengthening pro-market orientation contributes to a greater autonomy of economic activity in an enterprise, creates the possibilities to integrate consumption and production goods markets, concretizes market functions of an enterprise and supplements them with quantitative and qualitative relations. It also evokes and shapes competition mechanisms, sets high standards for the organizational structure of an enterprise, and forces the management to change their qualifications and attitudes. The article describes all the above changes and points to a new situation with respect to managing the enterprises in the light of changes in local relations and conditions and in the light of modifications in market functions of enterprises
Pro-market orientation in managing the enterprises